2022
DOI: 10.3390/nu14030427
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of “Moro” Blood Orange Citrus sinensis Osbeck (Rutaceae) Standardized Extract on Weight Loss in Overweight but Otherwise Healthy Men and Women—A Randomized Double-Blind Placebo-Controlled Study

Abstract: This study aimed to assess the efficacy of a blood orange Citrus sinensis standardized extract from “Moro” cultivar, on weight loss in overweight but otherwise healthy individuals. Anthocyanins and particularly cyanidin 3-glucoside, found in a large variety of fruits including Sicilian blood oranges, can help to counteract weight gain and to reduce body fat accumulation through the modulation of antioxidant, anti-inflammatory and metabolic pathways. In this randomized, double blind, placebo-controlled study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Although the literature reports increasing in weight gain and adiposity, we did not observe significant change in anthropometric parameters throughout the study. Briskey et al (2022) and Cardile et al (2015) showed significant reduction of body mass, BMI, hip and waist circumferences, fat mass, and fat distribution in overweight adults however these studies used Moro orange extract daily for 3 or 6 months. As in these studies, we also observed significant changes in the cardiometabolic markers in response to MOJ intake, especially in women with insulin resistance.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the literature reports increasing in weight gain and adiposity, we did not observe significant change in anthropometric parameters throughout the study. Briskey et al (2022) and Cardile et al (2015) showed significant reduction of body mass, BMI, hip and waist circumferences, fat mass, and fat distribution in overweight adults however these studies used Moro orange extract daily for 3 or 6 months. As in these studies, we also observed significant changes in the cardiometabolic markers in response to MOJ intake, especially in women with insulin resistance.…”
Section: Discussionmentioning
confidence: 88%
“…Several recent studies have investigated the benefits of blood orange juice intake, especially of the Moro variety ( Dorna et al, 2021 ; Nishioka et al, 2021 ; Ribeiro et al, 2021 ; Briskey et al, 2022 ; Santana et al, 2022 ; Capetini et al, 2023 ). However, the effects of MOJ on the gut microbiota profiles have not been investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more than 700 ANCs and derivatives have been identified from the natural world and processed food (He & Giusti, 2010; Veitch & Grayer, 2008), of which 6 are more common, including cyanidins, delphinidins, pelargonidin, peonidin, petunidin, and malvidin (Routray & Orsat, 2011). It has been clinically documented that ANCs possess diversified health‐promoting properties, such as anti‐inflammatory (do Rosario et al., 2021), anti‐obesity (Briskey et al., 2022), antioxidant (Cai et al., 2020), hypoglycemic (Wedick et al., 2012), and hypolipidemic (Zhang, Xu, et al., 2020). Obesity is considered to be a multifactorial disease characterized by excessive accumulation of fat (Kivimäki et al., 2022), and hyperglycemia is one of its serious complications, which seriously endangers human health.…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent flavonoids are flavonols, which are found naturally in plant vacuoles as glycoside derivatives ( Xing et al., 2021 ). Most citrus species are incapable of producing anthocyanins, but they are excellent study materials for flavanones and flavones in fruit ( Fabroni et al., 2016 ; Briskey et al., 2022 ). Plant growth, adaptability, signal transduction, and resistance to biotic and abiotic stressors are all impacted by flavonoids ( Li and Schluesener, 2017 ; Li et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%